Pembangunan Nilai Karakter Berbasis Rabbani pada Sistem Pendidikan di SMP IT Permata Kota Probolinggo - Susanti, Anindya Putri; Hidayah, Ulil (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
Character education based on Rabbani values ​​is a solution in facing the challenges of moral crisis in the digital era. This study aims to explore the application of school management in building Rabbani character of students at SMP Islam Terpadu (SMPIT) Permata Kota Probolinggo. The main focus of this study is to identify the Rabbani character values ​​applied, the implementation of character education programs, and evaluation techniques used in supporting the formation of student character. This study uses a qualitative approach with interview, observation, and documentation methods. The results of the study indicate that SMPIT Permata applies Rabbani values ​​such as honesty, responsibility, and discipline through integration in the curriculum, religious activities, and extracurricular activities. Educational programs such as reading Al-Ma'surat, congregational prayer, and social activities play an important role in internalizing these values. Evaluation is carried out with a point system that reflects student behavior and regular supervision to ensure the effectiveness of the program. This study provides insight into the importance of school management in building student character based on Islamic values, relevant to the challenges of the digital era. These findings are expected to be a reference in the development of educational character in various educational institutions.